Maimonides - Rudavsky, T. M. (Blackwell great minds., 2010)
A thorough and accessible introduction to Maimonides, arguably one of the most important Jewish philosophers of all time. This work incorporates material from Maimonides' philosophical, legal, and medical works, providing a synoptic picture of Maimonides' philosophical range.: Maimonides was, and remains, one of the most influential and important Jewish legalists, who devoted himself to a reconceptualization of the entirety of Jewish law; Offers both an intellectual biography and an exploration of the most important philosophical works in Maimonides' corpus; Persuasively argues that Maimonides.